UMP and Aspen Technology will expand collaboration in technology field - Halizan, Mohmood (UMPSA, 2022)
KUANTAN, 19 January 2022 - Universiti Malaysia Pahang (UMP) and Aspen Technology (AspenTech) will expand university and industry collaboration in academics, research, industry networking and community.